73.6k views
3 votes
1 upon sec A -tan a minus one upon cos A is equal to 1 upon Cos A minus one upon sec a + tan a prove it​

User Marcoo
by
5.1k points

1 Answer

1 vote

Explanation:

1/(seca-tana) - 1/cosa=1/cosa -1/(seca+tana)

There are many ways to solve this, let's take a look at a simple one

1/(seca-tana) + 1/(seca+tana) =1/cosa + 1/cosa

((seca-tana)+(seca+tana))/(sec^2a-tan^2a)=2/cosa

(seca-tana+seca+tana)/1=2*1/cosa

2seca=2seca

User Catrinel
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.